How Water Makes Us Human : Engagements with the Materiality of Water. - Attala, Luci (Materialities in anthropology and archaeology., 2019)
This book provides a novel cross-disciplinary approach to water, demonstrating the role water plays in shaping human lives. It uses anthropological information about water in Kenya, Wales and Spain to show how what water does in those areas has influenced the way that people can be with it.